Uporabnost kartiranja vinogradov kot metode za ugotavljanje prostorskih značilnosti termalnega pasu - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
In three peri-Pannonian regions in east Slovenia was tested method of determining spatial features of thermal belt by means of a detailed mapping of vineyards. The results corroborated the applicability of the method, however also exposed some of the methodćs limitations. It is suitable primarily for the areas with a lasting winegrowing tradition and with the population well informed about the local climate conditions. It yields good results in landscapes having strongly dissected landforms. The obtained results reflect spatial characteristics of thermal belt particularly at the beginning of the growth in spring when vine is most sensitive to frosts.
Keywords: climatology; klimatologija; microclimate; mikroklima; temperatura; topography; relief; temperaturni obrat; vinogradi; Slovenia; Slovenija